PKCε activator protects hippocampal microvascular disruption and memory defect in 3×Tg-Alzheimer’s disease mice with cerebral microinfarcts - Wang, Huaixing; Zhang, Zongxiu; Hongpaisan, Jarin (Frontiers in Aging Neuroscience, 2023)
Current evidence suggests that microvessel disease is involved in Alzheimer's disease (AD).Cerebrovascular disease correlates with cardiovascular disease and is complicated in ≈40% of AD patients. The protein kinase C (PKC) e activator DCPLA can stimulate human antigen (Hu) R that prevents degradation and promotes the translation of mitochondrial Mn-superoxide dismutase (MnSOD) and vascular endothelial growth factor-A (VEGF) mRNAs. To induce brain microinfarcts, we injected triple transgenic (3xTg) and wild-type (WT) control mice with microbeads (20µm caliber) into common carotid arteries, with or without the DCPLA-ME (methylester) for 2 weeks. After water maze training, mice at 16 months old were examined for confocal immunohistochemistry at a single cell or microvessel level in the hippocampal CA1 area, important for spatial memory storage, and in the dorsal hippocampus by Western blots. In 3xTg mice without cerebral microinfarcts, an accelerating age-related increase in (mild) oxidative stress and hypoxia inducible factor (HIF)-1a, but a reduction in VEGF, mitochondrial transcription factor A (TFAM), and MnSOD were associated with capillary loss. The change was less pronounced in arterioles. However, in 3xTg mice with cerebral microinfarcts, increasing arteriolar diameter and their wall cells were related with the strong oxidative DNA damage 8-hydroxy-2′-deoxyguanosine (8-OHdG), apoptosis (cleaved caspase 3), and sustained hypoxia (increased HIF-1a and VEGF/PKCe/extracellular signal regulated kinase or ERK pathway). Microocclusion enhanced the loss of the synaptic marker spinophilin, astrocytic number, and astrocyte-vascular coupling areas and demyelination of axons. DCPLA-ME prevented spatial memory defect; strong oxidative stress-related apoptosis; sustained hypoxia (by reducing HIF-1a and VEGF); and exaggerated cell repair in arteriolar walls, pericapillary space dilation, neuro-glial-vascular disruption, and demyelination. In conclusion, in 3xTg mice with cerebral microinfarcts, sustained hypoxia (increased HIF-1e and VEGF signals) is dominant with arteriolar wall thickening, and DCPLA has a protective effect on sustained hypoxia.